POLA KONSUMSI MAKANAN SUMBER HEWANI DAN STUNTING PADA ANAK USIA 6-60 BULAN DI 5 POSYANDU WILAYAH KELURAHAN BUGEL TAHUN 2023 - Hikmah, Agnia Nurul; Sari Nasrianti, Citra; Dara Avindharin, Pundra (Jurnal Nusantara Madani, 2023)
Background: Stunting is a chronic malnutrition problem that can affect physical growth and cognitive development in children, which has negative consequences in reducing academic achievement and reducing productivity as adults. Based on preliminary studies, there are 23% stunting cases in 5 posyandu in the Bugel sub-district area, the prevalence rate exceeds the national stunting rate. Subjects and methods: This research is a quantitative study with a cross-sectional study design, using a sample of 82 children aged 6-60 months in several posyandu in the Bugel sub-district area. This research uses bivariate analysis with the chi-square test. Results: There were 23.2% cases of stunting, 28.2% of boys were stunted and 18.6% of girls were stunted. There is a significant relationship between consumption of animal protein sources and stunting, p-value=0.003 (p-value≤0.05), OR=6.52. Consumption of meat and chicken was independently associated with stunting, while consumption of fish, shrimp and chicken eggs was not associated with stunting. Conclusion: Children aged 6-60 months who consume less animal source food are 6.5 times more likely to experience stunting than children who consume enough animal source food. Keywords: Stunting, Animal Sources Food, Toddler.